Human neuroblastoma: from basic science to clinical debut of cellular oncogenes - Schwab, Manfred (The Science of nature, 1999)
MYCN, which identifies a group of patients who have a particularly dire prognosis. Amplified MYCN is used today as a prognostic marker on which therapy design is based to a large extent. An unusual aspect of neuroblastoma is the high rate at which tumors regress spontaneously, even in infants with extensive liver involvement and numerous subcutaneous nodules. Identifying the molecular and cellular basis of spontaneous regression could result in improved therapeutic approaches. Neuroblastoma is a model tumor with many fascinating aspects but has remained a challenge to the pediatric oncologist